Physical and numerical modelling of offshore foundations under combined loads - Martin, C; C. M. Martin (1994)
In addition to vertical loads, the foundations of offshore structures are subjected to horizontal loads and overturning moments as a result of environmental (wind and wave) loading. The behaviour of circular footings on cohesive soil under conditions of combined vertical, horizontal and moment (V, H, M) loading is the primary concern of this thesis. A programme of physical model tests, involving combined loading of circular footings on reconstituted Speswhite kaolin, is reported. The shape of footing used is typical of the "spudcan" foundations of independent leg jack-up drilling platforms. Previous experience with combined loading of footings on sand has revealed that the observed load:displacement behaviour is best understood, and theoretically modelled, in terms of work hardening plasticity theory. The present tests on clay confirm this, and the results are interpreted to give empirical expressions for (i) the combined load yield surface in V:H:M space, and (ii) a suitable flow rule to allow prediction of the corresponding footing displacements (z, h, θ) during yielding. Extension to a complete plasticity model is achieved using theoretical stiffness factors to define elastic behaviour, and theoretical lower bound bearing capacity factors (derived specifically for this work) to define the size of the yield surface as a function of vertical penetration. The predictive capabilities of the numerical model are evaluated by retrospective simulation of various footing tests. Finally some plane frame structural analyses of a representative jack-up unit are described; some of these analyses incorporate the plasticity-based numerical model of spudcan footing behaviour under combined loads.